Antioxidant Activity of Polyphenolic Plant Extracts - Stagos, Dimitrios; Stagos, Dimitrios (Basel, Switzerland MDPI - Multidisciplinary Digital Publishing Institute, 2021)
(3z(BAntioxidant Activity of Polyphenolic Plant Extracts(3y (Bis a collection of scientific articles regarding polyphenols, that is, substances occurring naturally in plants and exhibiting many beneficial effects on human health. Among polyphenols$1 (Binteresting biological properties, their antioxidant activity is considered the most important. This book brings together experts from different research fields on topics related to polyphenols, such as their isolation and purification, assessment of their antioxidant activity, prevention from oxidative stress-induced diseases and use as food additives. The polyphenols used in the present studies are derived from a great variety of plants, ranging from well-known species to rare ones that are only found in specific regions. Moreover, some of the studies provide evidence that polyphenols may be used for the prevention and treatment of common diseases such as diabetes mellitus, Alzheimers$1 (Bdisease, cardiovascular and intestinal diseases. Importantly, in several of the studies (3z(Bgreen extraction methods(3y (Bfor the isolation of polyphenols were developed using modern technologies, where few or no organic solvents were used, in order to minimize environmental and health impacts.s
English
Keywords: Research & information: general; Biology, life sciences; green leafy vegetables; effect of cooking; polyphenols; antioxidant activity; Averrhoa bilimbi; Oxalidaceae; DPPH; xanthine oxidase; LC-QTOF-MS/MS; molecular docking; tentative bioactive constituents; Dialium indum; exocarp; seed; antioxidant; phenolic acids; amino acids; GC-MS analysis; AGN; FIR; phenolic; flavonoid; antioxidant capacity; antimicrobial activity; polyphenol compounds; bixin; rosemary extracts; method validation; HPLC; food matrices; fruit vinegar; phenolics; organic acid; Ladastacho; characterisation; properties; HPLC/ESI-MS; HS-SPME/GC-MS; beneficial use; antimicrobial; hydroxytyrosol; rosemary; pomegranate; fish; volatile compounds; Rosa canina; Rosa sempervivens; Pyrocantha coccinea; antioxidants; endothelial cells; glutathione; almond skins; bioavailability; waste by-products; flavonoids; oxidative stress; human; reactive oxygen species